(untitled) (Confluenţe Bibliologice, 2026)
This article examines the credibility and relevance of online information, highlighting the importance of source veriﬁcation in today’s digital environment. It explores criteria such as source authority, data currency, and message coherence, and considers the impact of misinformation on public opinion.